ANALISIS KUANTITATIF DOKUMEN REKAM MEDIS PASIEN RAWAT INAP KASUS BEDAH DI RSUD KANJURUHAN KEPANJEN - miftachul ulum (ITKM WIDYA CIPTA HUSADA, 2019)
ABSTRACK In a complete medical record obtained information that can be used for various purposes among which is as a tool for analysis and evaluation of the quality of services provided by the hospital. In improving the quality of service required for control of the charging document medical records. Quantitative analysis is one of the programs maintain quality by comparing all the records that exist in the medical record with the established standards. This study aims to determine the completeness of the medical record documents inpatient surgical cases through quantitative analysis. This study used quantitative descriptive approach. From the results of this study demonstrated completeness review is based on the identification of the patients is 25% and the incompleteness review patient identification is 75%. Based on the completeness of reporting critical review is 45% and the incompleteness of the reviews reporting that matters is 55%. Based on the completeness review authentication is 79% and the incompleteness review authentication is 21%. Based on the completeness of the documentation review is 56% and the incompleteness review documentation is 44%. To reduce the number of incomplete charging high medical records, should the Kanjuruhan Kepanjen hospital create standards and procedures in more detail about the charging document in the medical record that can then be disseminated to the nursing unit, in addition to the medical record unit proposes to create and attach a sticker containing the appeal